The prognostic significance of serum lactate dehydrogenase to albumin ratio in pancreatic ductal adenocarcinoma - Bilge, Hüseyin; Başol, Ömer; Demir, Baran; Oğuz, Abdullah (Acta Medica, 2023)
Objective: This study was performed to investigate the prognostic role of lactate dehydrogenase/albumin ratio (LAR) and pancreatic ductal adenocarcinoma (PDAC) with initial curable resection treatment. Materials and Methods: This retrospective study was conducted with the data of patients with resectable PDAC. The (ROC) analysis showed that the optimal sill value for pretreatment LAR was 91.43 and this threshold value was used in other analyses. Univariate and multivariate analyses were performed to determine the prognostic factors for overall survival (OS). Results: Our study consisted of 70 patients with a mean age of 59.5±13.2 years and 37 (52,9%) women. OS was 50 months in LAR <91.43 (n = 32) patients and 27,7 months in LAR≥91.43 (n=38) patients, respectively. Kaplan–Meier curves showed that LAR≥91.43 was significantly associated with worse OS (p=0.029). Multivariate analyses proved that LAR was an independent predictor in resectable PDAC patients (p=0.017). Conclusion: Our results showed that a high pre-treatment LAR level was a unfavorable prognosticator in PDAC patients undergoing curative resection. LAR has the potential to be a prognostic biomarker in clinical practice.